Corrective polishing of freeform optical surfaces in an off-axis three-mirror imaging system - Huang, Dengpeng; et al. (International Journal of Advanced Manufacturing Technology, 2017)
The application of freeform surface in the off-axis three-mirror imaging system can greatly improve its optical performance. However, it is difficult for fabrication of freeform optical surface to high precision by traditional machining technology. This paper focuses on the corrective polishing of the primary mirror and tertiary mirror, which are fabricated on one monolithic substrate and described by NURBS-based freeform surfaces, in an off-axis three-mirror imaging system. The integrated polishing process system is proposed for polishing the two mirrors on the 4-axis CNC polishing machine by use of spherical polishing tool. The tool influence function (TIF) module, polishing path generation and dwell time calculation module included in the integrated polishing process system are described respectively. The material removal on the measurement line of part surface is predicted to validate the dwell time calculation algorithm. The polishing experiments of the primary mirror and tertiary mirror are performed to verify the proposed integrated polishing process system.
Keywords: Tool influence function; Polishing path generation; Dwell time; Freeform optical surface; Off-axis three-mirror imaging system